Pharmacoeconomic aspects of oral vinorelbine application: a budget impact analysis considering the new registered price - D. A. Ivanov (Фармакоэкономика, 2021)
Objective: comparative assessment of the economic effect of oral vinorelbine when used as indicated, taking into consideration the new registered price.Material and methods. A clinical-economic study was performed to compare active platinum-containing chemotherapy regimens of the first line for stage IV non-small-cell lung cancer with oral vinorelbine and pemetrexed as well as first-line chemotherapy regimens for metastatic breast cancer presented with oral vinorelbine and ixabepilone alone. A systematic search for information in medical databases was carried out, the cost estimate was made out in accordance with the recommendations of The Center for Healthcare Quality Assessment and Control of the Ministry of Health of the Russian Federation. The direct medical costs were estimated, formed on the basis of the dosage, frequency and dosage regimen of the compared drugs, based on the data of the State Register of maximum selling prices, clinical guidelines for the studied nosologies, and instructions for medical use. The comparison of the economic effect of the studied drugs was carried out in pairs using the cost minimization method with a sensitivity analysis. Further, the calculations of the amounts of reimbursement of medical care provided were made using each of the compared drugs. An economic assessment of the economic effect of oral vinorelbine was carried out taking into consideration the change in the price of the drug and a budget impact analysis with a sensitivity analysis.Results. It was determined that the use of oral vinorelbine provides financial savings for a medical organization at the amount of 246,042.34 rubles per 6 cycles of chemotherapy for each patient with stage IV non-small-cell lung cancer compared with the use of pemetrexed, and 558,659.32 rubles per year – for the treatment of each patient with metastatic breast cancer compared with ixabepilone. The results of the budget impact analysis showed that the indication of oral vinorelbine saved 3,287,470.56 rubles for the budget fund considering the change in the cost of 1 mg of the drug for a hypothetical population of patients with stage IV non-small-cell lung cancer in 1000 people. This would create the possibility of therapy for additional 15 patients with this diagnosis. The indication of oral vinorelbine in first-line chemotherapy of metastatic breast cancer for a similar target population would save 18,355,043.96 rubles for the budget fund, which makes it possible to treat 15 more patients with this diagnosis.Conclusion. The use of oral vinorelbine is associated with the saving of financial resources of a medical organization. In addition, the reimbursement for medical care provided from the compulsory medical insurance funds when using regimens with oral vinorelbine is primarily lower than for comparison drugs. Thus, the use of regimens with oral vinorelbine is more beneficial for the payer (the Federal Compulsory Health Insurance Fund) and for the medical organization. The change in the cost of the drug is associated with an increase in the availability of medical care for patients with stage IV non-small-cell lung cancer and patients with metastatic breast cancer.